Antibiotic treatment of biofilm infections. Issue 4 (April 2017) - Ciofu, Oana; Rojo‐Molinero, Estrella; Macià, María D.; Oliver, Antonio
Abstract : Bacterial biofilms are associated with a wide range of infections, from those related to exogenous devices, such as catheters or prosthetic joints, to chronic tissue infections such as those occurring in the lungs of cystic fibrosis patients. Biofilms are recalcitrant to antibiotic treatment due to multiple tolerance mechanisms (phenotypic resistance). This causes persistence of biofilm infections in spite of antibiotic exposure which predisposes to antibiotic resistance development (genetic resistance). Understanding the interplay between phenotypic and genetic resistance mechanisms acting on biofilms, as well as appreciating the diversity of environmental conditions of biofilm infections which influence the effect of antibiotics are required in order to optimize the antibiotic treatment of biofilm infections. Here, we review the current knowledge on phenotypic and genetic resistance in biofilms and describe the potential strategies for the antibiotic treatment of biofilm infections. Of note is the optimization of PK/PD parameters in biofilms, high‐dose topical treatments, combined and sequential/alternate therapies or the use antibiotic adjuvants.